1997
DOI: 10.1016/s1074-7613(00)80367-2
|View full text |Cite
|
Sign up to set email alerts
|

A Requirement for the Rho-Family GTP Exchange Factor Vav in Positive and Negative Selection of Thymocytes

Abstract: The T cell repertoire is shaped by positive and negative selection of thymocytes that express low levels of T cell receptor (TCR) and both CD4 and CD8. TCR-mediated signals that determine these selection processes are only partly understood. Vav, a GDP-GTP exchange factor for Rho-family proteins, is tyrosine phosphorylated following TCR stimulation, suggesting that it may transduce TCR signals. We now demonstrate that mice lacking Vav are viable and display a profound defect in the positive selection of both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
261
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 266 publications
(282 citation statements)
references
References 67 publications
21
261
0
Order By: Relevance
“…Furthermore, up-regulation of the activation marker CD69 in response to peptide was similarly impaired in Vav1 -/-cells (not shown). This was consistent with previous observations that mutation of Vav1 reduces a number of TCR signaling pathways in thymocytes but does not completely abrogate them [6,14].…”
Section: Reduced Sensitivity Of Vav1 -/-Thymocytes To Tcr Stimulationsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, up-regulation of the activation marker CD69 in response to peptide was similarly impaired in Vav1 -/-cells (not shown). This was consistent with previous observations that mutation of Vav1 reduces a number of TCR signaling pathways in thymocytes but does not completely abrogate them [6,14].…”
Section: Reduced Sensitivity Of Vav1 -/-Thymocytes To Tcr Stimulationsupporting
confidence: 93%
“…Firstly, we and others have shown that Vav1 transduces signals to the activation of PLC + 1 and thus to an intracellular calcium flux [6,10,11,13,14]. This flux in turn activates the calcium-dependent protease caspian, which is required for LFA-1 clustering [28].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Its expression is restricted to cells of haematopoietic origin (Katzav et al, 1989). Targeted gene disruption revealed the importance of Vav1 for receptor-mediated proliferation and TCR-mediated positive selection (Fischer et al, 1995;Tarakhovsky et al, 1995;Zhang et al, 1995;Turner et al, 1997). Vav1 is furthermore important for the reorganization of the cytoskeleton and actin polymerization which contributes to the clustering of TCRs into patches and caps Holsinger et al, 1998).…”
Section: Introductionmentioning
confidence: 99%